Peningkatan Pengetahuan Kegawatdaruratan Pada Anak Pada Guru PAUD Di Puskesmas Sempor 1 - Yuwono, Podo; Ernawati, Ernawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The problem of accidents in children at school often occurs. At pre-school age, accidents contribute to morbidity and mortality in children, which are caused by traffic accidents, choking, drowning, falls and burns. The purpose of this community service is to increase the knowledge of PAUD teachers about emergencies in PAUD children. Lecture and discussion methods were used in this activity, using LCD media by measuring participants' knowledge before and after the activity took place. The participants were 26 PAUD teachers who were representatives of schools under the working area of the Sempor 1 Public Health Center. The results of the counseling showed an increase in the knowledge of PAUD teachers by 40%. Emergency counseling to early childhood has a positive impact on increasing the knowledge of PAUD teachers in the working area of the Sempor 1 Health Center